2003
DOI: 10.1046/j.1365-2249.2003.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen inhibits stimulus-induced proinflammatory cytokine synthesis by human blood-derived monocyte-macrophages

Abstract: SUMMARYHyperbaric oxygen (HBO) is 100% oxygen administered at elevated atmospheric pressure to patients with inflammatory diseases. We developed an in vitro model to investigate the effects of HBO on stimulus-induced proinflammatory cytokine transcription and translation. Human blood-derived monocytemacrophages were stimulated before being transferred to an HBO chamber where they were incubated at 97·9% O 2 , 2·1% CO 2 , 2·4 atmospheres absolute, 37 ∞ C. Controls were maintained in the same warm room at normox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 30 publications
5
99
0
1
Order By: Relevance
“…Hence, Desmarquest et al observed a decrease in several inflammatory markers in alveolar macrophages exposed to hyperoxia [9]. This effect seems to be consistent with hypobaric oxygen therapy (HBOT) studies carried out in ex vivo cell cultures [3,30,54]. These findings are also in agreement with studies demonstrating that HBOT attenuates pro-inflammatory cytokine production of systemic inflammation in animal models [32,57,58].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Hence, Desmarquest et al observed a decrease in several inflammatory markers in alveolar macrophages exposed to hyperoxia [9]. This effect seems to be consistent with hypobaric oxygen therapy (HBOT) studies carried out in ex vivo cell cultures [3,30,54]. These findings are also in agreement with studies demonstrating that HBOT attenuates pro-inflammatory cytokine production of systemic inflammation in animal models [32,57,58].…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, Lahat et al [30] also observed a decrease in the secretion of TNF- in macrophages of rats exposed to HBOT for 90 min. Furthermore, in a study by Benson et al [3], IL-1 and TNF- synthesis in macrophages was inhibited by a 90-min HBOT exposure. All these findings are also in agreement with studies demonstrating that HBOT attenuates proinflammatory cytokine production in animal models of systemic inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, currently presented results indicate both a beneficial therapeutic effect, manifested by a subjective and objective improvement of the clinical condition of the patients, as well as an inhibitory effect on the dynamics of changes in the tested laboratory parameters, particularly immunoglobulin E and C3 complement component. Furthermore, these observations are consistent with the findings of other researchers dealing with the use of hyperbaric oxygenation as a therapeutic option for other groups of diseases associated with an immune activation and inflammatory cascade [11,15,16,17,18,19,20,21].…”
Section: Research Results and Discussionsupporting
confidence: 81%
“…In general, the effects of HBO are similar to those accomplished with immunosuppressant drugs, leading to a decrease in inflammatory response in the body [4,35], which is achieved by reducing the synthesis of inflammatory mediators such as nitric oxide (NO) [36,37], prostaglandin E2 (PGE2) [38,39], tumour necrosis factor α (TNF-α), interleukin 1β and 12 (IL-1β, IL-12) and interferon γ (IFN-γ) [9,16,18,23,38,40,41], as well as a reduced expression of cyclooxygenase-type 2 mRNA (COX-2), an enzyme involved in inflammation [42]. In addition to the inhibitory effect on the synthesis of proinflammatory cytokines, the consequence of hyperbaric oxygen therapy is an increased release of antiinflammatory cytokines such as interleukin 10 (IL-10) [9,43].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…HBOT at 1.0 or 2.5 ATA for 30 and 60 min enhanced 3T3/J2 fibroblast cell growth while at 2.5 ATA for 120 min, it exerted a pro apoptotic effect. HBOT may potentially contribute to the inhibition of fibroblasts by reducing IL-1b and TNF-α production [13,15,16]. HBOT may be useful in the treatment for OSF by promoting fibroblast apoptosis and inhibiting fibroblast activation [17] [ …”
Section: Collagen Metabolismmentioning
confidence: 99%